Synthesis and Characterization of Poly(o-toluidine) in Ionic Liquid and Lanthanum Chloride - LI†, SHENGQI; TANG, LI; TANG, RONG; KAN*, JINQING (Asian Journal of Chemistry, 2009)
Poly(o-toluidine) of high conductivity (10.14 S cm-1) was synthesized by chemical process in a solution containing LaCl3 and ionic liquid. The conductivity, UV-Vis, FTIR spectra, X-ray diffraction and thermogravimetric analysis were investigated. The results of conductivity showed that the cooperative effect of La3+ and ionic liquid remarkably improved the conductivity of poly(o-toluidine). Meantime, the energy gaps of the π-π* and quinoid ring transitions are affected by the cooperative effect of La3+ and ionic liquid in UV-Vis. The peak of Q-NH+-B or B-NH+-B in poly(o-toluidine) doped with La3+ shifts to longer wavelength in FTIR spectra in the presence of ionic liquid. La3+ and ionic liquid hardly affect the crystallinity of poly(o-toluidine).